Method for recovering whole-size lepidolite through combination of multistage magnetic separation and synergistic flotation

Through the combined process of specific composite collectors and multi-stage magnetic separation-flotation, the problems of poor resource endowment, fine embedded particle size and complex process in iron lithium mica ore dressing technology are solved, and efficient recycling and environmentally friendly production of full-grain iron lithium mica are achieved.

CN120532644APending Publication Date: 2025-08-26HUNAN ZIJIN LITHIUM IND CO LTD +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510833516.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The existing iron lithium mica ore dressing technology has problems such as poor resource endowment, fine embedded particle size, complex process flow, high cost and large environmental pollution, making it difficult to achieve efficient, low-cost and environmentally friendly comprehensive utilization of lithium resources.

Method used

A specific composite collector (composed of sodium dodene sulfonate, amino acid methylthiohydroxypropionate, amphoteric polyacrylamide polymer, carboxyethylene diphosphate and polyethylene glycol) is used to combine magnetic separation-flotation combined process to recover the whole-grain grade iron lithium mica through multi-stage magnetic separation and flotation methods to optimize the ore dressing process.

Benefits of technology

It realizes efficient recycling of full-grain lithium iron mica, reduces production costs, reduces environmental pollution, improves the comprehensive utilization rate of lithium resources, and provides sustainable ore dressing solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of mineral flotation, and particularly discloses a method for recovering whole-fraction iron lepidolite through combination of multi-stage magnetic separation and synergistic flotation. Comprising a matched compound collecting agent which is composed of sodium dodecenesulfonate, amino acid methyl thiohydracrylate, an amphoteric polyacrylamide polymer, carboxyethylidene diphosphonic acid and polyethylene glycol, and efficient recovery of whole-size-fraction iron lepidolite is achieved by matching with a corresponding magnetic separation-flotation combined process. The compound collecting agent generates static electricity and physical and chemical adsorption on the iron lepidolite through specific groups such as sulfonic acid groups, carboxyl groups, amino groups, acylamino groups and phosphate groups, exerts excellent selectivity and collecting functions, generates a dispersion effect and a chelating flocculation effect on micro-fine-particle iron lepidolite, and well cooperates with multi-stage magnetic separation to recover whole-particle-size iron lepidolite, so that the recovery rate of the whole-particle-size iron lepidolite is increased, and the recovery rate of the whole-particle-size iron lepidolite is increased. And the existing combined beneficiation process of the iron lepidolite is optimized, the cost and the environmental influence are reduced, and technical support is provided for sustainable development of lithium resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mineral flotation, and in particular relates to a method for recovering lithophile mica in all particle sizes through multi-stage magnetic separation combined with coordinated flotation. Background Art

[0002] Lithium is a core raw material for new energy batteries, and ferrolithium mica provides a crucial supplement to the lithium resource supply. As a key lithium resource, with the rapid growth in lithium demand, ferrolithium mica research and development has gained increasing attention. Ferrolithium mica occurs in pegmatites, granites, and greisen, often coexisting with quartz, feldspar, tantalite, beryl, cassiterite, and wolframite. It occurs in granular or flaky form, with a relatively fine embedded particle size, increasing the difficulty of mineral processing.

[0003] At present, the development and utilization of ferrolithium mica mainly depends on mineral processing technology, of which magnetic separation and flotation are the two main methods. Based on the weak magnetic properties of ferrolithium mica, it can be separated by magnetic separation by taking advantage of the magnetic difference between it and gangue minerals. Flotation is another important method for ferrolithium mica beneficiation. The key lies in the selection of collectors and the control of flotation conditions. The two are usually used in combination to form a magnetic separation-flotation combined process, which effectively solves the problem of separating ferrolithium mica from gangue minerals and improves the comprehensive utilization rate of lithium resources (high mud lepidolite Full-Grain-Size Magnetic-Flotation Combined Mineral Processing, Wang Rongrui et al., Chinese Journal of Engineering Science, Vol. 47, No. 4, pp. 642-653, April 2025; Experimental Study on Comprehensive Recovery of Ferrolithium Mica, Quartz and Feldspar from a Lithium-Bearing Granite, Yuan Jinming et al., Chemical Minerals and Processing, pp. 1-13, October 2024; Comprehensive Recovery Technology Study of a Low-Grade Ferrolithium Mica Ore in Jiangxi, Zou Yaowei et al., Nonferrous Metals (Mineral Processing), No. 5, pp. 85-89, May 2019).

[0004] Although iron lithium mica beneficiation technology has made certain progress, the following problems still exist: First, the iron lithium mica resource endowment is poor and the embedded particle size is fine, which makes the beneficiation more difficult; second, the beneficiation process of iron lithium mica is complicated and costly, usually requiring multiple stages of grinding and multiple stages of separation. The process is complicated and consumes a lot of reagents; third, the pressure on environmental protection is high, and the wastewater and waste residue generated during the beneficiation process will cause certain pollution to the environment.

[0005] In the future, ferrolithium mica beneficiation technology will develop towards high efficiency, environmental friendliness, and low cost. Mainstream research will focus on developing highly efficient and selective collectors, optimizing magnetic separation-flotation combined processes, and strengthening flotation wastewater treatment technology to increase the comprehensive utilization of lithium resources and achieve clean production. The development and utilization of ferrolithium mica resources is crucial for alleviating the imbalance between lithium supply and demand in my country. Further research into beneficiation technology is needed to reduce production costs and achieve green and sustainable development. Summary of the Invention

[0006] In order to solve the above technical problems, the present invention provides a method for recovering lithophile mica of full particle size by combining multi-stage magnetic separation with coordinated flotation. By preparing a specific compound collector (composed of sodium dodecene sulfonate, amino acid methylthiohydroxypropionate, amphoteric polyacrylamide polymer, carboxyethylene diphosphoric acid, and polyethylene glycol) and combining it with a corresponding magnetic separation-flotation combined process, efficient recovery of lithophile mica of full particle size can be achieved.

[0007] The technical solutions of the present invention are as follows: A composite collector is composed of sodium dodecene sulfonate, amino acid methylthiohydroxypropionate, amphoteric polyacrylamide polymer, carboxyethylene diphosphoric acid and polyethylene glycol.

[0008] Preferably, based on 100 parts of the total mass of the active ingredients, the ingredients include 25-30 parts of sodium dodecene sulfonate, 10-15 parts of amino acid methylthiohydroxypropionate, 5-15 parts of amphoteric polyacrylamide polymer, 5-10 parts of carboxyethylene diphosphate, and 35-45 parts of polyethylene glycol.

[0009] These active components are the key to the composition of the compound collector, based on which the good effect of the compound collector can be achieved. The content range of each component is based on the basic properties contained in most of the currently discovered full-size iron lithium mica ores, and according to the mechanism of action of each component, the two jointly determine the range of these contents. The above content range can also ideally achieve the final collection effect of the compound collector in combination with the mineral processing process. If it is not within the above content range, the effect of the compound collector on general full-size iron lithium mica ores is slightly worse. The range of each component indicated in the invention is applicable to the currently more common iron lithium mica. Based on the above, the selection of the content of each component of the compound collector is more important, and the content range is applicable to the selection of most full-size iron lithium mica.

[0010] Preferably, the sodium dodecene sulfonate is linear sodium dodecene sulfonate, which has good biodegradability, meets modern environmental protection requirements, and has a wide range of applications.

[0011] Preferably, the amino acid methylthiohydroxypropionate is at least one of glycine methylthiohydroxypropionate, alanine methylthiohydroxypropionate and glutamic acid methylthiohydroxypropionate.

[0012] Preferably, the amphoteric polyacrylamide polymer is at least one of an acrylamide-acrylic acid-cationic monomer copolymer, an acrylamide-methacrylic acid-cationic monomer copolymer, and an acrylamide-sulfonic acid monomer-cationic monomer copolymer.

[0013] Preferably, the carboxyethylene diphosphoric acid is at least one of monocarboxyethylene diphosphoric acid, dicarboxyethylene diphosphoric acid and polycarboxyethylene diphosphoric acid.

[0014] Preferably, the molecular weight specification of the polyethylene glycol is at least one of PEG-200, PEG-300, and PEG-400.

[0015] In the composite collector of the present invention, sodium dodecene sulfonate serves as an anionic surfactant. Its hydrophobic end (long carbon chain) and hydrophilic end (sulfonic acid group) enable selective electrostatic, physical, and chemical adsorption on the interface of lithophile mica, reducing surface tension and thus achieving emulsification, wetting, and dispersion functions. Furthermore, the hydrophobic end of the agent can bind to oils or hydrophobic substances, while the hydrophilic end interacts with water, forming a stable emulsified system and providing a certain dispersing effect.

[0016] Amino acid methylthiohydroxypropionate is an amino acid derivative containing a thio group. It combines the biocompatibility of amino acids with the functional groups of methylthiohydroxypropionic acid, exhibiting chelating and antioxidant properties, and exhibiting good biocompatibility. The carboxyl (-COOH) and amino (-NH2) groups in this compound can chemically bond with metal ions (such as calcium, magnesium, and iron) on the surface of lithophile mica. Under appropriate pH conditions, it can flexibly carry either a positive or negative charge, adsorbing to the surface of lithophile mica through electrostatic interactions. Furthermore, the amino and carboxyl groups in the amino acid can form hydrogen bonds with hydroxyl groups or water molecules on the mineral surface, enhancing adsorption capacity. This allows for effective synergy with sodium dodecene sulfonate in the selective capture of lithophile mica, while also enhancing bubble stability.

[0017] Amphoteric polyacrylamide polymer is a high-molecular-weight polymer containing both cationic and anionic groups. It selectively adjusts its charge distribution based on the surface charge of lithophile mica, and the dominance of the anionic and cationic groups is controlled by the acid-base environment of the solution, thereby generating electrostatic adsorption on the lithophile mica surface. Simultaneously, the carboxyl, sulfonic, or amino groups in the polymer chemically bond with metal ions on the mineral surface to form stable surface compounds, which synergistically interact with the amino acid methylthiohydroxypropionate on the lithophile mica surface. Furthermore, the acylamino groups (-CONH2) in the polymer form hydrogen bonds with hydroxyl groups or water molecules on the lithophile mica mineral surface, enhancing adsorption capacity.

[0018] Carboxyethylene diphosphate is an organic compound containing carboxyl and phosphate groups with excellent chelating properties. The carboxyl (-COOH) and phosphate (-PO3H2) groups it contains can chemically bond with metal ions on the surface of lithophile mica minerals and adsorb on the positively charged mineral surface through electrostatic action under specific pH conditions. The carboxyl and phosphate groups can form hydrogen bonds with hydroxyl groups or water molecules on the surface of lithophile mica minerals, further enhancing the adsorption capacity.

[0019] Polyethylene glycol is a widely used water-soluble polymer. Its large molecular weight, good thermal stability, and terminal functional groups such as methyl and hydroxyl groups can increase the water solubility of insoluble substances. In the compound collector, it mainly serves as a reaction solvent to promote the dissolution and fusion of the various components, and as a phase transfer catalyst to promote multiphase reactions, accelerating the production process of the compound collector. In addition, it is recyclable, low-volatile, non-toxic, and biodegradable, which can significantly reduce the impact of chemical synthesis on the environment. Polyethylene glycol plays a catalytic role due to its large molecular weight, good thermal stability, and terminal functional groups such as methyl and hydroxyl groups. The working principle is to promote the dissolution and fusion of other components in the compound collector, and as a phase transfer catalyst to promote the catalytic multiphase reaction between various components other than itself, thereby accelerating the production process of the compound collector.

[0020] The present invention also provides a method for preparing a composite collector, which is as follows: Sodium dodecene sulfonate, amino acid methylthiohydroxypropionate, amphoteric polyacrylamide polymer, carboxyethylene diphosphoric acid and polyethylene glycol components are mixed, heated for a period of time, and the unreacted solvent is removed to obtain the product.

[0021] Preferably, the heating temperature is 65-75° C., more preferably 70° C.; the heating time is 3.5-4.5 hours, more preferably 4 hours, to promote the dissolution and homogenization of the components.

[0022] Preferably, a rotary evaporator is used to remove unreacted polyethylene glycol solvent to obtain a composite collector with a higher concentration.

[0023] Preferably, in actual use, the compound collector is prepared into a solution with a mass concentration of 2-3%; more preferably, it is prepared into a 2.5% solution to efficiently utilize the collector and improve the collection efficiency.

[0024] Some of the components of the composite collector exhibit physical synergy and chemical reactions, but the intensity of the chemical reactions is relatively weak, resulting in the composite collector existing as a physical mixture. This allows each component to retain its original chemical properties relatively intact. With the exception of polyethylene glycol, the other components exhibit synergistic effects.

[0025] The present invention also provides the use of the composite collector in the multi-stage magnetic separation and flotation recovery of full-size lepidolite. Furthermore, a method for multi-stage magnetic separation and efficient flotation recovery of full-size lepidolite is provided, which specifically comprises the following steps: The lepidolite ore is ground, and an adjusting agent is added to adjust the pH value of the solution to a weak alkalinity of 8-9. A compound collector is then added for rapid flotation, followed by classification to obtain coarse and fine particle products. The fine particle product is used as the ore for multi-stage magnetic separation to obtain magnetically separated lepidolite tailings as flotation feed, which is then subjected to slurry adjustment. During the slurry adjustment stage, an adjusting agent is added to adjust the pH value of the solution to a weak alkalinity of 8-10. A compound collector is then added for aeration flotation to obtain lepidolite concentrate and tailings.

[0026] The present invention synergistically combines the two mineral processing methods of multi-stage magnetic separation and flotation. The coarse-grained lepidolite is firstly quickly floated out, and then the fine-grained ore samples are classified for multi-stage magnetic separation. The magnetic separation concentrate is then floated, assisted by a suitable compound collector, so as to efficiently capture and comprehensively utilize the iron lepidolite of all particle sizes.

[0027] Preferably, the separation particle size of lithophile mica is targeted at all particle sizes, including coarse and fine particle sizes, especially the fine-grained lithophile mica, and is efficiently separated in coordination with multi-stage magnetic separation.

[0028] Preferably, the grinding fineness of the iron lithium mica ore is -0.074mm (less than 200 mesh) and the content is 50-60%.

[0029] Preferably, the particle sizes of the coarse-grained and fine-grained products are greater than or equal to 0.038 mm (400 mesh) and less than 0.038 mm, respectively.

[0030] Preferably, the adjusting agent is sodium hydroxide, the pH value of the solution is adjusted to about 8.5, and the slurry concentration is 35-55%.

[0031] The purpose of adding sodium hydroxide is, on the one hand, to adjust the pH value of the slurry to weak alkalinity, providing a suitable solution environment for the action of the compound collector; on the other hand, the addition of sodium hydroxide will have a certain activation effect on the surface of lithophile mica, forming a differentiated dissolution surface with the gangue minerals, which will be conducive to the selective adsorption of the compound collector, thereby realizing the multi-stage magnetic separation and flotation synergistic and efficient recovery of full-size lithophile mica.

[0032] Preferably, the rapid flotation is roughed at least once, the amount of the added regulator is 100-120 g / t, the amount of the compound collector is 300-400 g / t; and the 400 mesh (0.038 mm) standard sieve is selected for grading.

[0033] The reason for selecting the amount of compound collector added in rapid flotation is mainly based on the ore properties of the iron lithium mica itself. In addition, rapid flotation targets the coarser particles and a small amount of finer particles in the full-size iron lithium mica. Therefore, the amount added is slightly lower than the amount used in the subsequent rough selection of finer particles. This is because fine-grained minerals consume more reagents than coarse particles, which is determined by factors such as their own specific surface area and the influence of mineral slime.

[0034] Preferably, the weak magnetic separation properties of ferroalite dictate that it be recovered in stages, requiring at least two stages of magnetic separation. Additional stages are optional, but excessive magnetic separation can lead to the entrainment of other gangue. Multi-stage magnetic separation includes at least two high-intensity roughing stages; the magnetic field strength for high-intensity roughing stage I is 1.0-1.5 T, and the magnetic field strength for high-intensity roughing stage II is 1.5-1.8 T. This is due to the magnetic properties of ferroalite, necessitating two high-intensity roughing stages for recovery. The increased magnetic field strength allows the first roughing stage to yield higher-grade ferroalite, avoiding contamination by other weakly magnetic minerals and reducing entrainment. The increased magnetic field strength in the second roughing stage aims to recover as much of the full size of ferroalite as possible for subsequent flotation purification and recovery.

[0035] Preferably, the beneficiation process of aeration flotation includes one roughing, at least one cleaning and at least two scavenging processes; the amount of adjusting agent added in the roughing process of aeration flotation is 100-120 g / t, the amount of compound collector added is 400-600 g / t, the amount of compound collector added in the one scavenging process is 200-300 g / t, the amount of compound collector added in the two scavenging processes is 100-150 g / t, and no reagent is added in the one cleaning process.

[0036] The reason for selecting the above-mentioned aerated flotation process is based on the properties of the ore entering the roughing, that is, the content and state of all the ferrolithium mica in the magnetic concentrate. The process of selecting a one-roughing, two-sweeping, and one-fine process can obtain better flotation indicators. The addition amount of the compound collector is also based on the ore properties of the magnetic concentrate. On the other hand, this flotation is mainly aimed at the finer particles in the full-size ferrolithium mica, so the addition amount is slightly higher than the roughing amount when the particles are coarser. This is also due to the influence of the properties of the fine-grained mineral itself. Its specific surface area is much larger than that of the coarse particles. The compound collector needs to be adsorbed on the mineral surface to work. Therefore, fine particles require more reagents to achieve the same surface coverage. In addition, fine particles have high surface energy and are prone to form agglomerates or covers, which makes the adsorption efficiency of the reagent lower.

[0037] The beneficial effects of the present invention are: The composite collector of the present invention uses unique sulfonic acid, carboxyl, amino, amido and phosphate groups to generate electrostatic, physical and chemical adsorption on iron lithium mica, exerting excellent selectivity and collecting functions, and produces a dispersion effect and chelating flocculation effect on fine iron lithium mica. It also has good biodegradability and environmental advantages, and can cooperate well with multi-stage magnetic separation to recover iron lithium mica of full particle size. The recovery rate of the raw ore can reach more than 60%, optimize the existing combined mineral processing process of iron lithium mica, reduce costs and environmental impact, and provide technical support for the sustainable development of lithium resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The present invention is a flow chart of a mineral processing process in which the composite collector is applied to multi-stage magnetic separation and coordinated flotation to recover full-size iron lithium mica. DETAILED DESCRIPTION

[0039] The following is a further detailed explanation of the composite collector and its process flow of the present invention in conjunction with specific examples. In the present invention, all the reagents used are purchased from commercial sources.

[0040] The raw ore used in the following examples is lepidolite from a mine in Jiangsu Province. Chemical multi-element analysis revealed that the elements or components included Li2O, Al2O3, Fe2O3, and K2O, with grades of 1.06%, 19.36%, 9.04%, and 5.19%, respectively. Particle size analysis of the ore sample revealed that the -0.074 mm (less than 200 mesh) particle size content was 49.83%, and the particle size was uniform, primarily consisting of lepidolite and feldspar quartz, as well as intergrowths with tantalum-niobium ore.

[0041] The specific preparation and use process of the composite collector used in the following examples is as follows: Take 25 parts of linear sodium dodecylsulfonate, 15 parts of alanine methylthiohydroxypropionate, 10 parts of acrylamide-methacrylic acid-cationic monomer polymer, 5 parts of dicarboxyethylene diphosphate, and 45 parts of polyethylene glycol with a molecular weight specification of PEG-300, heat to 70°C, and maintain this temperature for 4 hours to promote the dissolution and homogenization of each component. Finally, use a rotary evaporator to remove the unreacted solvent polyethylene glycol PEG-300 to obtain a higher concentration of composite collector. In actual use, it is prepared into a solution with a mass concentration of 2.5%.

[0042] In the following examples, the adjusting agent sodium hydroxide was prepared into an aqueous solution with a mass concentration of 2% and added.

[0043] Example 1 See attached Figure 1The process flow chart shows that the lithophora ore is ball milled to a fineness of -0.074mm (less than 200 mesh) and a content of 55%. 100g / t of sodium hydroxide (a conditioning agent) is added and stirred for 3 minutes. Then, 400g / t of a compound collector is added and stirred for another 3 minutes before rapid flotation. The ore is then classified into two particle sizes: +400 mesh (greater than or equal to 400 mesh) and -400 mesh (less than 400 mesh). The +400 mesh is directly used as tailings, while the -400 mesh fraction is used as feed for magnetic separation.

[0044] For magnetic separation, the magnetic field strength was adjusted to 1.2T for strong magnetic roughing I, and then to 1.7T for strong magnetic roughing II. The concentrates from both were combined to form a magnetic separation concentrate. Flotation was then performed by first adding 120g / t of sodium hydroxide and stirring for 3 minutes. Afterwards, a compound collector (600g / t) was added and stirred for 3 minutes before roughing. The tailings were then subjected to a primary scavenging process with 300g / t of the compound collector added, followed by a secondary scavenging process with 150g / t. Primary concentrating was then performed without adding any reagents. The resulting flotation indices are shown in Table 1.

[0045] From the flotation indicators in Table 1, it can be found that under the conditions of multi-stage magnetic separation and coordinated flotation, the flotation of the full-size lepidolite is more obvious. The Li2O recovery rate of the flotation concentrate obtained by rapid flotation reaches 12.62%, the Li2O grade of the flotated lepidolite concentrate reaches 1.98%, and the Li2O recovery rate reaches 49.24%. This reflects the comprehensive recovery of the full-size lepidolite by the process flow and the good selective capture ability of the composite collector for the lepidolite under the combined process.

[0046] Table 1

[0047] Example 2 The raw lithophora mica ore is ball milled to a fineness of -0.074mm (less than 200 mesh) with a content of 55%. 100g / t of sodium hydroxide (a conditioning agent) is added and stirred for 3 minutes. Then, 300g / t of a compound collector is added and stirred for another 3 minutes before rapid flotation. The ore is then classified into two particle sizes: +400 mesh (greater than or equal to 400 mesh) and -400 mesh (less than 400 mesh). The +400 mesh is directly used as tailings, while the -400 mesh product is used as feed for magnetic separation.

[0048] For magnetic separation, the magnetic field strength was first adjusted to 1.3 T for strong magnetic roughing I, and then to 1.8 T for strong magnetic roughing II. The concentrates from both were combined to form a magnetic separation concentrate. Flotation was then performed by adding 100 g / t of sodium hydroxide and stirring for 3 minutes. Afterwards, 400 g / t of a compound collector was added and stirred for 3 minutes before roughing. The tailings were then subjected to primary scavenging with 200 g / t of the compound collector, followed by secondary scavenging with 100 g / t. Primary concentrating was performed without adding any reagents. The resulting flotation indices are shown in Table 2.

[0049] From the flotation index of Table 2, it can be found that, under the conditions of multi-stage magnetic separation and synergistic flotation, the present invention appropriately increases the magnetic field intensity of strong magnetic separation and reduces the dosage of the compound collector. The overall recovery rate of full-size iron lithium mica changes little, the flotation concentrate Li2O recovery rate obtained by rapid flotation is 11.24%, the Li2O recovery rate in the magnetic tailings is 3.42%, the flotation lithium concentrate Li2O grade reaches 1.98%, the Li2O recovery rate reaches 48.32%, and the total concentrate recovery rate reaches 59.56%, reflecting the selective capture ability of the compound collector for full-size iron lithium mica under the combined process of multi-stage magnetic separation and flotation synergy. Compared with Example 1, the dosage of the compound collector in Example 2 is reduced, and it can be seen that the recovery rate is reduced, and the capture effect of full-size lithium mica is reduced.

[0050] Table 2

[0051] By comparing the test results of Example 1 and Example 2, it can be seen that the method of the present invention is aimed at full-size iron lithium mica, and the multi-stage magnetic separation and flotation combined mineral processing process is coordinated with the corresponding compound collector, which achieves a good separation effect on the iron lithium mica, has certain feasibility value, and provides a reference for subsequent combined mineral processing technology.

[0052] The concentrate obtained by the process of combining the composite collector of the present invention with multi-stage magnetic separation and coordinated flotation has generally good and stable grade and recovery rate indicators, and has great advantages over other types of collectors currently used. The mineral processing process of only multi-stage magnetic separation and no flotation can only be used for iron lithium mica with certain special raw ore properties. For ordinary iron lithium mica such as that used in the present invention, the mineral processing process test results of only multi-stage magnetic separation and no flotation are very poor. However, the flotation effect of only flotation and no multi-stage magnetic separation is slightly better than the process effect of only multi-stage magnetic separation and no flotation. However, since iron lithium mica has a certain weak magnetic separation, the process of only flotation and no multi-stage magnetic separation will consume more composite collectors, and cannot achieve the purpose of economic efficiency.

[0053] In summary, the collaborative multi-stage magnetic separation and flotation combined beneficiation process of the present invention provides a composite collector with excellent capture effect and relatively stable and a corresponding multi-stage magnetic separation-flotation collaborative beneficiation process flow for the efficient recovery and utilization of full-size iron lithium mica ore.

Claims

1. A composite collector, characterized in that: Its components include sodium dodecene sulfonate, amino acid methylthiohydroxypropionate, amphoteric polyacrylamide polymer, carboxyethylene diphosphoric acid and polyethylene glycol.

2. The composite collector according to claim 1, wherein: Based on 100 parts of the total weight of the active components, the following ingredients are prepared: 25-30 parts of sodium dodecene sulfonate, 10-15 parts of amino acid methylthiohydroxypropionate, 5-15 parts of amphoteric polyacrylamide polymer, 5-10 parts of carboxyethylene diphosphoric acid, and 35-45 parts of polyethylene glycol.

3. The composite collector according to claim 1, wherein: The sodium dodecene sulfonate is linear sodium dodecene sulfonate; the amino acid methylthiohydroxypropionate is at least one of glycine methylthiohydroxypropionate, alanine methylthiohydroxypropionate and glutamic acid methylthiohydroxypropionate; the amphoteric polyacrylamide polymer is at least one of acrylamide-acrylic acid-cationic monomer copolymer, acrylamide-methacrylic acid-cationic monomer polymer and acrylamide-sulfonic acid monomer-cationic monomer copolymer; the carboxyethylene diphosphoric acid is at least one of monocarboxyethylene diphosphoric acid, dicarboxyethylene diphosphoric acid and polycarboxyethylene diphosphoric acid; the molecular weight specification of the polyethylene glycol is at least one of PEG-200, PEG-300 and PEG-400.

4. The method for preparing the composite collector according to any one of claims 1 to 3, characterized in that: Sodium dodecene sulfonate, amino acid methylthiohydroxypropionate, amphoteric polyacrylamide polymer, carboxyethylene diphosphoric acid and polyethylene glycol components are mixed, heated for a period of time, and the unreacted solvent is removed to obtain the product.

5. The preparation method according to claim 4, characterized in that: The heating temperature is 65-75°C, more preferably 70°C; the heating time is 3.5-4.5 hours, more preferably 4 hours.

6. The preparation method according to claim 4, characterized in that: In actual use, the compound collector is prepared into a solution with a mass concentration of 2-3%; more preferably, it is prepared into a solution with a mass concentration of 2.5%.

7. Use of the composite collector according to any one of claims 1 to 3 or the composite collector obtained by the preparation method according to any one of claims 4 to 6, characterized in that: The compound collector is used in multi-stage magnetic separation and synergistic flotation to recover full-size iron lithium mica.

8. A method for recovering full-size iron lithium mica by multi-stage magnetic separation and flotation, characterized in that: The method comprises the following steps: grinding lepidolite ore, adding the composite collector according to any one of claims 1 to 3 for rapid flotation, and then classifying to obtain coarse-grained and fine-grained products; subjecting the fine-grained products as ore to multi-stage magnetic separation to obtain magnetically separated lepidolite tailings as flotation feed, performing slurry preparation, and then adding the composite collector for aeration flotation to obtain lepidolite concentrate and tailings.

9. The method according to claim 8, characterized in that: After grinding, an adjusting agent is added to adjust the solution pH value to 8-9; during the slurry preparation process, an adjusting agent is added to adjust the solution pH value to 8-10; the adjusting agent is sodium hydroxide; the preferred adjusted solution pH value is 8.5; the preferred slurry concentration is 35-55%.

10. The method according to claim 9, characterized in that: The multi-stage magnetic separation includes at least two strong magnetic roughing separations; preferably, the magnetic field strength of the strong magnetic roughing separation I is 1.0-1.5T, and the magnetic field strength of the strong magnetic roughing separation II is 1.5-1.8T; preferably, the beneficiation process of the aeration flotation includes one roughing separation, at least one concentration and at least two scavenging separations; preferably, the amount of the adjusting agent added in the roughing separation during the aeration flotation process is 100-120g / t, the amount of the compound collector added is 400-600g / t, the amount of the compound collector added in the first scavenging process is 200-300g / t, the amount of the compound collector added in the second scavenging process is 100-150g / t, and no reagent is added in the first concentration process.

Citation Information

Cited By

  • Battery material lithium carbonate production method and production equipment

    CN121292478A

  • A method for producing a battery material lithium carbonate and an apparatus for the production

    CN121292478B